Clinostatic Hypertension and Orthostatic Hypotension - Lagi, Alfonso (Clin Cardiol, 2010)
BACKGROUND: The association of clinostatic hypertension (CH) and orthostatic hypotension (OH) is described as the “Hyp‐Hyp phenomenon,” and it has been found in about 5.5% of hypertensive patients and in up to 50% of patients with OH. The importance of CH/OH in clinical practice is mainly due to the presence of troublesome symptoms, end‐organ damage, and difficulties in its clinical management. HYPOTHESIS: The review focuses on the clinical problem of CH and review the international literature for the best management, including the diagnostic work‐up and the taylored treatment for this kind of patients. METHODS: A systematic review of the literature was conducted through MEDLINE research to focus the main controversial issues about CH/OH. Included topics: (1) the diagnostic work‐up, (2) the association with dysautonomic failure and syncope, and (3) the treatment options and prevention of end‐organ damage. RESULTS: Current standard reference for OH diagnosis includes functional assessment of the cardiac vagal nervous system and the sympathetic adrenergic system. The association with dysautonomic failure and with syncope needs further investigation. Pharmacologic treatment of OH is aimed at controlling symptoms rather than restoring normotension. Midodrine is the only medication that has been put to multicenter placebo‐controlled trial and subsequently approved by the U.S. Food and Drug Administration (FDA) for OH treatment. Short‐acting oral antihypertensive agents at bedtime should be considered in patients with severe, sustained CH. CONCLUSIONS: Data obtained from the literature review showed that clinical diagnosis of the Hyp‐Hyp phenomenon is relatively simple, but it remains more difficult to establish the causal disease. In our opinion, it is advisable to define simple diagnostic standards for the selection of patients at risk of dysautonomic impairment so that a subsequent highly specific diagnostic work‐up could be initiated. Copyright © 2010 Wiley Periodicals, Inc.